5E Model in Science Classroom A Shift towards Constructivism - Jain, Anil Kumar; Bhardwaj, Shweta (JOURNAL OF INDIAN EDUCATION, 2012)
Learning by doing is the essence of science and for science classroom, constructivism seems promising learning philosophy. Constructivism is the buzz word of learner-centred education, today we find textbooks structured on the philosophy of constructivism. Unfortunately, the type of pedagogical approach students facing in science classrooms is still old fashioned, behaviouristic one. Science teacher is an important person in structuring and guiding students’ understanding of living in the changing world. They play the role of facilitator and help students to bridge between nature of science and inquiry practices. They also need to learn new ways of pedagogical sciences to promote scientific literacy based on inquiry-oriented classroom. For practising constructivist methods in science classrooms, there is need to restructure the curriculum of teacher education and to orient pre-service and in-service teachers towards using these constructivist strategies in classroom. In our country still prospective science teachers are practising their teaching based on contemporary teaching models of Herbart, Bloom indirectly emphasising behaviourism. These teachers use the oldest and the most traditional approach, deductive reasoning that focuses on the content of the science organised from general concepts to particular concepts, with less emphasis on the development of skills. Teachers need to change their lesson plan format from behaviourist to constructivist one. Several studies have shown that instructions based on 5E model has positive impact on academic achievement and attitude towards learning among students. In the light of these, in the present paper, the authors attempt to enlighten the 5E model based on constructivism and tries to comprehend its usage in our science classrooms for better understanding of scientific concepts.